2021
DOI: 10.1088/1741-4326/ac2d57
|View full text |Cite
|
Sign up to set email alerts
|

Structure-preserving particle-in-cell simulation of lower hybrid wave propagation and heating in the magnetic mirror

Abstract: This study presents the first-principle, structure-preserving electromagnetic particle-in-cell simulation of the lower hybrid wave (LHW) in magnetic mirror-confined plasmas. The behavior of LHW propagation and ion heating is studied and compared with the ray-tracing results. Two full-wave effects of LHW propagation in the mirror devices, the rotation of LHW and tunnel effects near the resonance, are revealed and discussed. Meanwhile, the ion heating near the resonance layer is presented. We first provide the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…6 shows mirror 160MHz LHW simulation results, which is close to the three dimensional (3D) electromagnetic particle-in-cell (PIC) simulations results in Ref. [17] as shown in Fig. 6(b) for both the ray trajectories and turning points.…”
Section: Mirror Lhw and Icwsupporting
confidence: 83%
See 1 more Smart Citation
“…6 shows mirror 160MHz LHW simulation results, which is close to the three dimensional (3D) electromagnetic particle-in-cell (PIC) simulations results in Ref. [17] as shown in Fig. 6(b) for both the ray trajectories and turning points.…”
Section: Mirror Lhw and Icwsupporting
confidence: 83%
“…Figure6: Mirror 160MHz LHW simulation results, which is close to the results in Ref [17]. of 3D PIC simulations (b), where the PIC data with E x < 10 is removed to make the figure more clear.…”
supporting
confidence: 77%
“…They involve helicon wave, lower hybrid fast and slow wave, applied for the current drive, plasma heating and plasma rotation in toroidal devices [9][10][11]. In addition, a recent study has demonstrated the effectiveness of stochastic ion heating of LHW in magnetic mirror devices, which opens a new aspect for ion heating studies in linear devices, such as tandem mirrors [12]. In addition, LHW is economical, which is very helpful for university research on fusion plasma heating.…”
Section: Introductionmentioning
confidence: 99%